2014
DOI: 10.19047/0136-1694-2014-73-95-120
|View full text |Cite
|
Sign up to set email alerts
|

Soils within the steppe and dry steppe zones under anomalous weather conditions in the last tens years

Abstract: Under consideration is the influence of climate changes (the air temperature rise in the cold 6 months especially in the winter and the increased atmospheric moistening in the warm 6 months) on regimes and properties of soils in dependence on zonal-provincial, geomorphological and lithological conditions as exemplified by the solonetz complex in the semi-desert Pre-Caspian plain and chernozems in central European Russia and southern regions of this country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…During the fi rst years after plowinge, there is a sharp change in their structural state, density of their structure, and aqueous-physical properties (Medvedev V, 2016). The studies, conducted in the Forest-Steppe of Ukraine demonstrated the norms for the changes in physical parameters of arable EVALUATING AGROGENIC STRUCTURIZATION OF SOIL VARIANTS UNDER DIFFERENT soils and terminal values for the parameters of their indices, provided for the forecast on productivity loss of agricultural crops under deterioration of the structural state and compaction (Medvedev V et al, 2012;Bulyhin S et al, 2014;Medvedev V et al;2014). The studies also determined the impact of multiple passages of heavy machinery in the fi elds on the decrease in the yield of agricultural crops which may range from 10 to 50 % (Bryk M, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…During the fi rst years after plowinge, there is a sharp change in their structural state, density of their structure, and aqueous-physical properties (Medvedev V, 2016). The studies, conducted in the Forest-Steppe of Ukraine demonstrated the norms for the changes in physical parameters of arable EVALUATING AGROGENIC STRUCTURIZATION OF SOIL VARIANTS UNDER DIFFERENT soils and terminal values for the parameters of their indices, provided for the forecast on productivity loss of agricultural crops under deterioration of the structural state and compaction (Medvedev V et al, 2012;Bulyhin S et al, 2014;Medvedev V et al;2014). The studies also determined the impact of multiple passages of heavy machinery in the fi elds on the decrease in the yield of agricultural crops which may range from 10 to 50 % (Bryk M, 2004).…”
Section: Introductionmentioning
confidence: 99%